Relationships between Occupational Therapy Practitioner Characteristics and Home Exercise Program Prescription for Clients with Neurological Injuries. Issue 4 (2nd October 2019) - Proffitt, Rachel
Abstract: There are no guidelines for the prescription of home exercise programs (HEPs) for clients with neurological injuries. However, 95% of occupational therapy practitioners prescribe HEPs. Two thousand anonymous surveys were distributed to occupational therapy practitioners. Data from the 352 returned, usable surveys were analyzed to determine trends in HEP prescription across practice settings and provider demographics. Occupational therapy practitioners in community-based settings tended to use more functional activities and the number of years in practice did not influence HEP dosage. These findings suggest a need for clear guidelines for varying practice settings to guide HEP prescription.